ANALYSIS OF BOYSUN EMBROIDERY AND ITS MEANINGS - S.A. Rakhimkulova; U.S. Rakhmatullayeva; A.N.Mamatmusayeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the study of Boysun applied art, one of the districts of the Surkhandarya region. In this regard, the study of Surkhandarya embroidery was based primarily on various data related to embroidery. The history of embroidery, the types of stitches used in embroidery and sewing techniques, and the study and research based on them.